Modern Gas-Based Temperature and Pressure Measurements - Pavese, Franco. (International Cryogenics Monograph Series, 2013)
This 2nd edition volume of Modern Gas-Based Temperature and Pressure Measurements follows the first publication in 1992. It collects a much larger set of information, reference data, and bibliography in temperature and pressure metrology of gaseous substances, including the physical-chemical issues related to gaseous substances. The book provides solutions to practical applications where gases are used in different thermodynamic conditions. Modern Gas-Based Temperature and Pressure Measurements, 2nd edition is the only comprehensive survey of methods for pressure measurement in gaseous media used in the medium-to-low pressure range closely connected with thermometry. It assembles current information on thermometry and manometry that involve the use of gaseous substances which are likely to be valid methods for the future. As such, it is an important resource for the researcher. This edition is updated through the very latest scientific and technical developments of gas-based temperature and pressure measurements using thermometry and manometry, and brings all of the techniques together under one cover. This book fills the gap in international literature, as no other recently published book provides a comprehensive survey for gaseous media closely connected with thermometry. Updates in this new edition include revised appendices and new chapters on Mutual Recognition Agreement of the Comit ̌International des Poids et Mesures and its main applications, and developments in the European Metrology Society.